Investigating Prospective Teachers’ Competences in Understanding Religious Dimensions in Poetry ‘Perang Pecah Lagi Di Gaza’ - Putri, Angela Suryani; Roziah, Roziah (Universitas Pendidikan Mandalika, 2024)
Religiosity refers to the extent of insight and knowledge one has about their religion, the strength of their belief in carrying out worship and following rules, and the depth of their absorption in their faith. Religiosity can be classified into several dimensions. According to Stark and Glock, these dimensions are divided into five categories: Religious Belief (The Ideological Dimension), Religious Practice (The Ritualistic Dimension), Religious Feeling (The Experiential Dimension), Religious Knowledge (The Intellectual Dimension), and Religious Effect (The Consequential Dimension). This research was conducted to provide an overview of religiosity as depicted in a literary work, a subject that has previously been rarely explored. The approach used in this study is a descriptive qualitative approach. Data collection was carried out using two techniques: the reading and note-taking technique and a questionnaire. The total number of religiosity dimensions analyzed in this study is 30, drawn from 15 poetry titles. The data reveal that the percentage distribution of religiosity dimensions is as follows: 53% for the belief dimension, 33% for the worship dimension, 10% for the knowledge dimension, 3% for the practice dimension, and 0% for the appreciation dimension. The findings of this study conclude that the belief dimension is the most dominant dimension in the poetry collection ‘Perang Pecah Lagi di Gaza’. Additionally, the study highlights the students' low understanding of exploration activities related to religiosity and its various dimensions.